Caracterização da microscopia de campo evanescente por reflexão interna total - Sabrina Ferreira dos Santos (2024)
The Total Internal Reflection Fluorescence (TIRF) is a powerfull evanescent field microscopy technique based on excitation of fluorophores by an electromagnetic evanescent field generated through the phenomenon of total internal reflection of an excitation light beam incident on the interface of two media of different refraction index. Due to the exponential decay of this evanescent field with distance, TIRF’s primary application is beased on the visualization and study of the dynamics, the structures and other biological phenomena that occur on the adhered cells’ plasma membrane in nanometric scale through the fluorescence analisis. In order to have access to this technique and characterize its physical parameters, in this work is presented a setup protocol for a homemade ‘through the objective’ TIRF using a blue diode laser at 488 nm coupled to the rear port of an inverted microscope. This protocol includes a quality test for this TIRF setup that consists in a qualitatively analisis of a fluorescence microbeads solution wich attest its effectiveness. The system characterization was performed following a second protocol based on the phenomena of frustrated total internal reflection that determines the evanescent field behavior with distance. This characterization, therefore, made possible the identification of variables capable of reducing the light scattering intrinsic to the setup and analyse the accuracy of incident angles mesurements.